Aerosol generation through phacoemulsification. Issue 9 (September 2020) - Lee, Hanbin; Naveed, Hasan; Ashena, Zahra; Nanavaty, Mayank A.
Abstract : Phacoemulsification was not an aerosol-generating procedure for aerosols of 10 μm or less with continuous power using 80% longitudinal, 100% torsional, or 80% longitudinal setting with HPMC on the surface. Abstract : Purpose: To evaluate whether phacoemulsification is an aerosol-generating procedure in an ex vivo experimental model. Setting: Sussex Eye Hospital, Brighton, United Kingdom. Design: Experimental study. Methods: In this ex vivo study on 15 porcine eyes, an optical particle counter was used to measure particles of 10 µm and less using the cumulative mode based on the 6 in-built channel sizes. The 2 parts of the study were to: (1) assess the efficacy of the particle counter in the theater environment where there are dynamic changes in temperature and humidity; and (2) to measure aerosol generation with 3 phacoemulsification settings: (i) continuous power with 80% longitudinal (5 eyes); (ii) continuous power with 100% torsional (5 eyes); and (iii) continuous power with 80% longitudinal with application of hydroxypropyl methylcellulose (HPMC) on the ocular surface (5 eyes). Five measurements were taken prephacoemulsification and 5 during phacoemulsification per eye therefore totaling 75 measurements. Results: Maximum aerosols were captured when the counter faced the aerosol source. There was no significant difference in aerosol generation of all sizes during each phacoemulsification setting with torsional, longitudinal, and longitudinal with HPMC ( P > .01). Combining data of all 3 phacoemulsification settings (150 measurements from 15 eyes), there was no significant difference comparing prephacoemulsification and during phacoemulsification for aerosols of 5 µm or less (1455 vs 1363.85, P = .60), more than 5 to 10 μm (1.5 vs 1.03, P = .43), and of 10 µm or less (1209 vs 1131.55, P = .60). Conclusions: Phacoemulsification did not generate aerosols of 10 μm or less with continuous power using 80% longitudinal, 100% torsional, and 80% longitudinal setting with HPMC on the surface.